Making simple things complicated using anti-inflammatory reliever therapy. Issue 4 (29th April 2020) - Lipworth, Brian; Kuo, Chris RuiWen; Chan, Rory
We appreciated reading the eloquent editorial from Beasley et al . [1], who make a cogent evidence-based case for using budesonide/formoterol (BUD/FM) on demand ( p.r.n .) as the preferred asthma reliever, in keeping with the latest GINA guidelines. They proffer what appears at first sight to be a pragmatic stepwise treatment algorithm and associated action plan for using BUD/FM p.r.n . as anti-inflammatory reliever (AIR)±maintenance therapy across Global Initiative for Asthma steps 1 to 3. Use more budesonide/formoterol when you need it, and less when you don't http://bit.ly/2PKsCOH